Fit for the court: Ottoman royal costumes and their tailors, from the sixteenth to eighteenth century - (:unkn) unknown (My University, 2012)
The collection at the Topkapi Palace Museum includes some three thousand items of royal clothing. Most of these belonged to the sultans and their immediate male relatives. According to a tradition that was established after the demise of Mehmed II (reigned 1451-81), clothes were packed and stored in the treasury after an individual's death. While some children's clothing has also survived, very few garments belonging to the women of the royal household were preserved. All royal costumes were made at the palace workshop, which at its height at the end of the sixteenth century employed close to seven hundred tailors. By drawing on extant palace record books and other rich archival materials dating from the sixteenth to the eighteenth century, this paper discusses the structure and organization of the royal tailors' workshop as well as the training of individuals who aspired to join it.